Effects of central electron cyclotron power on plasma rotation and on triggerless onset of NTMs in the TCV tokamak. (25th August 2015) - Lazzaro, E.; Nowak, S.; Sauter, O.; Canal, G.; Duval, B.; Federspiel, L.; Karpushov, A.N.; Kim, D.; Reimerdes, H.; Rossel, J.; Testa, D.; Wagner, D.
Abstract: Experiments in the TCV tokamak show that high power central electron cyclotron heating (ECH) and current drive (ECCD) produce significant direct modification of the plasma rotation profile, as well as an effect on the equilibrium current density profile. In a regime of unsteady rotation, these effects contribute to the onset of neoclassical tearing instabilities, in the absence of triggers such as sawteeth, edge localised modes (ELMS) or relevant 'error' fields. In turn the growing tearing modes' breaking axisymmetry provides a nonlinear magnetic torque which converts the power absorption in a co-directed rotation with a flattening of the profile at the rational surfaces. The experimental results are presented and discussed in the context of theoretical models of neoclassical toroidal viscosity and ion inertial effects.